Pengaruh Motivasi Belajar terhadap Kemampuan Menulis Pantun Bahasa Daerah - Hidayatun Nur (GERAM: Gerakan Aktif Menulis, 2021)
Writing ability is one of the language skills possessed by a person. One of the skills to write old poetry is pantun. Pantun develops in the people of the archipelago with a variety of regional languages. This study aimed to determine the effect of learning motivation on the ability to write local language rhymes. This study uses multiple linear regression analysis. From the research results, it can be seen that the learning motivation is in a good category and the ability to write local language pantun is in a good category. The motivation of learning showed an influence on the poetry writer's ability, which was proven that the significance value was 0.000 that smaller than the probability of 0.05. From the research results, it can be seen that the learning motivation contributed 49.4% to the ability to write regional language pantun, and other factors influenced the remaining 50.6%.